Hybrid Approach of a Complex Aneurysm of the Subclavian-Axillary-Brachial Axis: A Case Report. (November 2022) - Mendes, Daniel; Vaz, Carolina; Machado, Rui; Almeida, Rui
Background: Upper extremity arterial aneurysms are a rare, potentially limb-threatening disorder. Due to its rarity, the best treatment modality and outcomes are not entirely established; however, there is a consensus that open surgery is the first-line treatment. We present a complex case of an arterial aneurysm of the subclavian-axillary-brachial axis adequately treated using a hybrid surgical and endovascular treatment. Case Presentation: A 59-year-old man presented to the emergency department with acute ischemia of the right upper limb. An extensive thrombosed aneurysm of the subclavian-axillary-brachial axis was identified. The treatment was carried out in two stages. In the first phase, urgent limb revascularization was performed using the great saphenous vein to perform a subclavian-brachial artery bypass. Later, the aneurysm was excluded using a vascular plug and multiple coils. Successful treatment was achieved with no morbidity for the patient. Conclusions: Although the gold standard for treating upper limb aneurysms is open surgery, endovascular techniques can be a significant adjunct, reducing treatment morbidity and even mortality.